The turning point in 1985 : the history of appraisal and disposal of records in Iceland - Kristinsdóttir, Kristjana (2003)
Sumario: The article sets off with a brief summary of the history of appraisal and disposal of records as processed at the National Archives of Iceland (NAI) since its establishment in 1882 to present times. Rules on appraisal and disposal of records introduced in 1900, 1911, and 1916 were ignored and all records were kept. Status quo remained until 1985 when a new National Archives Act was passed. The appraisal and disposal process adopted then is described and explained. It included the publication of instructions on records management as well as forms relating to records management. The influence of acts of law on the appraisal and disposal process is explained. Finally the experience with the arrangement of organised appraisal in Iceland is described.